From Propaganda to Attraction: Reassessing the Role of the Public in the Newsreel Jornal Português (1938–1951) - Sampaio, S. (Historical Journal of Film, Radio and Television, 2022)
The Jornal Português: Revista Mensal de Actualidades was a newsreel produced between 1938 and 1951 for the SPN/SNI, the main organ of propaganda of the Portuguese Estado Novo (1933–1974). It therefore offers a privileged view into the relationship between the cinematographic field and the dictatorship of António de Oliveira Salazar (1889–1970), in its first years. Propaganda has, unsurprisingly, been the preferred angle of analysis, encouraging most scholars to treat these films as a vehicle of ideological indoctrination. The article argues that this approach relies (often unwittingly) on an outmoded concept of ‘mass communication’ that downplays the cinematic specificities of these films in two ways: by foregrounding government-led ‘hard topics’ to the detriment of ‘soft topics’, and by reducing onscreen images of the public to instances of political manipulation. I suggest, as an alternative, that we understand these topics and images within a ‘cinema of attractions’ framework, which acknowledges the central role the audience plays in the cinematic apparatus. In the absence of empirical work on these films’ reception, this kind of theoretical intervention enables us to recover the figure of the public in newsreels, and gain a better grasp of the Jornal Português as a filmic, rather than a journalistic, genre.